2022
DOI: 10.18860/ling.v16i2.11528
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of Humorous Discourse in Mind Your Language

Abstract: The primary purpose of this study is to reveal the function of humorous discourse identified in the Mind Your Language situation comedy series. The researcher adopted a descriptive qualitative approach to complete this humor research. The data were obtained from the script of that sitcom. The function of humorous discourse found in that sitcom was then classified based on Hay's framework, which divides the function of humor into three main functions: the function of solidarity, the function of power, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Another study by Fadhlina (2021) demonstrated that humor is also one of the popular methods used by Islamic preachers in spreading Islamic teachings. These studies are in line with Romadlani and Wijana's (2022) findings concerning humor used for the function of power. Furthermore, Marzolph (2011) explained how Islam perceives humor by exploring Qur'anic verses and Hadith about the approach to expressing humor and the history of Arab Muslims concerning the use of humor in their discourses.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study by Fadhlina (2021) demonstrated that humor is also one of the popular methods used by Islamic preachers in spreading Islamic teachings. These studies are in line with Romadlani and Wijana's (2022) findings concerning humor used for the function of power. Furthermore, Marzolph (2011) explained how Islam perceives humor by exploring Qur'anic verses and Hadith about the approach to expressing humor and the history of Arab Muslims concerning the use of humor in their discourses.…”
Section: Introductionsupporting
confidence: 89%
“…Humor is one of the communication features that researchers have investigated to disclose the way people use humor for specific functions or intentions in general as well as in religious contexts. In a general context, Romadlani and Wijana (2022) found out that the humor utterances used in Mind Your Language sitcom fulfill Hay's framework of the functions of humor which are solidarity function, power function, and psychological function. The function of humor is also examined in Islamic contexts.…”
Section: Introductionmentioning
confidence: 98%